Orman’s Internet Addiction Survey: a Preliminary Psychometric Study in an Universitary Andalusian Sample - Matas, Antonio (2015)
In recent decades several instruments have been developed to assess the behaviour of being continuously connected to Internet shown by some Internet users. The Internet Addiction Survey by Mc. Orman is one of them. Its psychometric properties are analysed in this article, using an incidental sample of university students. The results showed a satisfactory level of reliability and a one-dimensional underlying structure, with high correlation values with other instruments used for the same purpose. Its use is recommended in the study of Internet addiction.